Early and late response of Nematostella vectensis transcriptome to heavy metals. Issue 19 (12th September 2014) - Elran, Ron; Raam, Maayan; Kraus, Roey; Brekhman, Vera; Sher, Noa; Plaschkes, Inbar; Chalifa‐Caspi, Vered; Lotan, Tamar
Abstract Environmental contamination from heavy metals poses a global concern for the marine environment, as heavy metals are passed up the food chain and persist in the environment long after the pollution source is contained. Cnidarians play an important role in shaping marine ecosystems, but environmental pollution profoundly affects their vitality. Among the cnidarians, the sea anemone Nematostella vectensis is an advantageous model for addressing questions in molecular ecology and toxicology as it tolerates extreme environments and its genome has been published. Here, we employed a transcriptome‐wide RNA‐Seq approach to analyse N. vectensis molecular defence mechanisms against four heavy metals: Hg, Cu, Cd and Zn. Altogether, more than 4800 transcripts showed significant changes in gene expression. Hg had the greatest impact on up‐regulating transcripts, followed by Cu, Zn and Cd. We identified, for the first time in Cnidaria, co‐up‐regulation of immediate‐early transcription factors such as Egr1, AP1 and NF‐κB. Time‐course analysis of these genes revealed their early expression as rapidly as one hour after exposure to heavy metals, suggesting that they may complement or substitute for the roles of the metal‐mediating Mtf1 transcription factor. We further characterized the regulation of a large array of stress‐response gene families, including Hsp, ABC, CYP members and phytochelatin synthase, that may regulate synthesis of the metal‐binding phytochelatins instead of the metallothioneins that are absent from Cnidaria genome. This study provides mechanistic insight into heavy metal toxicity in N. vectensis and sheds light on ancestral stress adaptations.